Surface crystallization mechanism of n-hexane droplets. (15th January 2023) - Bian, Jiang; Ding, Gaoya; Guo, Dan; Cao, Hengguang; Liu, Yang; Cao, Xuewen
Abstract: Revealing the crystallization mechanism of alkane molecules is of great significance to promote the development of the natural gas liquefaction industry. Although many efforts have been made on the crystallization of chain molecules, the surface crystallization mechanism of short-chain alkanes has not yet been solved. In this paper, molecular dynamics simulations were employed to investigate the surface crystallization process of n-hexane nanodroplets and elucidate the surface crystallization mechanism. The results show that the crystallization process of supercooled heavy hydrocarbon droplets can be divided into two stages. The reduction of torsion energy and Lennard‒Jones energy makes important contributions to the droplet crystallization process. The molecules at the vapor-liquid interface tend to be arranged in an orderly manner, and the molecular principal axes are perpendicular to the interface. The molecules at the vapor-solid interface fluctuate strongly along their molecular axes. In addition, the entropy change value for the overall crystalline layer of n-hexane is approximately 1.4 times higher than that of the surface crystalline layer. It is proven that there is a significant energy gain in the surface crystalline layer, which is an important driving force for n-hexane crystallization. Highlights: The surface crystallization process of n-hexane was investigated at molecular level. The interfacial free energies at the equilibrium melting point were obtained. Surface crystallization mechanism of n-hexane droplets converges with entropy theory. There is a significant energy gain in the surface crystalline layer. The driving force for surface crystallization were elucidated.